2013
DOI: 10.1088/1741-2560/10/4/046007
|View full text |Cite
|
Sign up to set email alerts
|

Integrated wireless fast-scan cyclic voltammetry recording and electrical stimulation for reward-predictive learning in awake, freely moving rats

Abstract: We have developed an integrated wireless voltammetry system for measuring dopamine concentration and providing electrical stimulation. The developed wireless FSCV system is proven to be a useful experimental tool for the continuous monitoring of dopamine levels during animal learning behavior studies of freely moving rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, DA and NA can be distinguished by targeting different microelectrodes to their respective pathways (Park et al, 2011). Fast cyclic voltammetry can also be used to measure the effects of stimulated DA release (O'Connor and Lowry, 2012) and has recently been further refined by the development of an integrated wireless system which allows both recoding and stimulation in awake, freely moving rats (Li et al, 2013). However, although this represents an important technological advance and rats adapt well to the implants necessary for voltammetry studies, less invasive procedures are of course preferable.…”
Section: New Methods Of Workingmentioning
confidence: 99%
“…However, DA and NA can be distinguished by targeting different microelectrodes to their respective pathways (Park et al, 2011). Fast cyclic voltammetry can also be used to measure the effects of stimulated DA release (O'Connor and Lowry, 2012) and has recently been further refined by the development of an integrated wireless system which allows both recoding and stimulation in awake, freely moving rats (Li et al, 2013). However, although this represents an important technological advance and rats adapt well to the implants necessary for voltammetry studies, less invasive procedures are of course preferable.…”
Section: New Methods Of Workingmentioning
confidence: 99%
“…The physical characteristics and electrochemical performance of this wireless DA and 5-HT sensing system, in comparison with other reported devices, is summarized in Table S1. Balancing between physical dimensions and electrochemical performance, our device utilizes CV techniques and has demonstrated the capability of detecting multiple neurotransmitters simultaneously with similar LODs compared to previously reported works. For example, the Wireless Instantaneous Neurotransmitter Concentration Sensing System (WINCS) was developed to monitor neurotransmitters in animals.…”
Section: Resultsmentioning
confidence: 93%
“…We found that cocaine enhanced DA release in vivo with an EC 50 of approximately 0.25 mg/kg, which is similar to what others have reported (Li et al . ). This is consistent with its rewarding concentrations.…”
Section: Discussionmentioning
confidence: 97%